Simple preparation Au/Pd core/shell nanoparticles for 4-nitrophenol reduction - Srisombat L. (2017)
© 2016 Elsevier B.V. In this study, various sizes and chemical compositions of Au/Pd nanoparticles with core/shell structure were successfully prepared by employing a simple successive reduction method without addition of any stabilizer. The optical properties, morphologies, chemical compositions and crystal structures of the synthesized particles were fully characterized by using a combination of UV–vis spectroscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, wavelength-dispersive X-ray spectroscopy, selected area electron diffraction and X-ray diffraction techniques. The catalytic activities of the synthesized Au/Pd nanoparticles for 4-nitrophenol reduction were also investigated and compared with monoatomic Au and Pd nanoparticles. The highest catalytic activity of bimetallic was obtained from AuPd 4 nanoparticles. With comparable size, Au/Pd nanoparticles provide better catalytic activity than those of monometallic Au and Pd. However, lower catalytic activities of Au/Pd nanoparticles are shown compared with that of smaller-size Au nanoparticles. This study also reveals that the size effect of catalysts plays important role on catalytic activity more than only changing their chemical constituents.